Hälfte des Lebens (Studia theodisca, 2019)
The paper is the written version of a previous lecture, held on the occasion of a new translation of Hölderlin’s poem Hälfte des Lebens by the world-known French scholar Jean-Pierre Lefebvre, who was a student of Paul Celan. The Sorbonne Emeritus, former member of the Board of the Hölderlin-Gesellschaft Tübingen and translator of Goethe, Hölderlin, Hegel and Heine, as well as of Rilke, Kafka, Brecht and Celan, discusses here in detail the task of the poet in his times, and of his interpreters and adapters. His new translation, A moitié de la vie, is reproduced at the bottom of the essay.